The “D” Word And Covid-19; Outcome Of Indoor Diabetics With Covid-19 In Tertiary Care Hospital. - Shams, Nadia; Meraj, Lubna; Aqeel, Muhammad; Andaleeb, Hina; Qadri, Lama; Qadri, Syed Muhammad Hameez (Journal of Rawalpindi Medical College, 2025)
OBJECTIVE: COVID-19 has been a global challenge. Diabetes is a frequent co-morbid in Covid cases having a complex bidirectional relationship. This study aims to determine the outcome of COVID-19 cases with diabetes vs. non-diabetics. METHODS: This observational study was conducted at RIHS Islamabad (June–Dec. 2020) after ethical approval. Adult indoor confirmed (PCR positive) COVID cases of both genders were included by consecutive sampling. Patients <18 years of age, having gestational diabetes, drug-induced diabetes and Cushing’s syndrome were excluded. The study included 75 Covid cases with diabetes (group A) and 75 Covid non-diabetics (group B). Diabetes was labelled based on glycated haemoglobin and blood sugars. Patients were managed as per recommendations and followed till discharge or expiry. Details are documented on a specially designed proforma. Data was analyzed by SPSS V-22 with significant p<0.05. The chi-square test was applied to study the association of diabetes in Covid cases with expiry, duration of hospital stay, disease severity and need for mechanical ventilation. RESULTS: Among 150 cases of Covid; there were 54(36%) females and 96(64%) males. The mean age was 58+13 years (range 27-92 years). The mean age of those cases who expired was 60.77+12.78 years vs. 56.73+13.40 years in those who were discharged (p>0.05). Obesity was observed in 41(27.3%), hypertension in (35.3%), ischemic heart disease in 26(17.3%), asthma in 11(7.3%), COPD in 7(4.7%), chronic kidney disease in 7(4.7%), hypothyroidism in 5(3.3%), These co-morbid conditions had no association with mortality. 9(6%) cases had mild Covid, 97(64.7%) moderate and 44(29.3%) had severe Covid. Higher frequency of moderate 41(54.7%) and severe 29(65.9%) Covid was found in diabetics. Death was observed in 14(14.4%) moderate and 34(77.3%) severe Covid (p<0.0001). The mean duration of hospital stay was 13+7.7 days (1-45 days) having no association with mortality. The need for invasive ventilation and duration of admission were comparable between the two groups. Total 102(68%) cases were discharged and 48(32%) expired. 30(62.5%) of deceased were diabetics vs. 18(37.5%) non-diabetics (p=0.036). CONCLUSION: Diabetes is commonly observed comorbidity in COVID-19 cases and is significantly associated with disease severity and mortality. Patients with both diabetes and COVID-19 require close monitoring and careful management. Additionally, older age and obesity are important risk factors that further contribute to the severity of the disease and the risk of mortality in diabetic patients with COVID-19.